Simulating hybrid dynamic systems. - Rabbath, C.A.
This article presents the problem of inaccuracy involved in the conventional simulations, at fixed time steps, of event-based systems and then proposes the use of a new Simulink toolbox, known as the RT-events blockset, to significantly reduce the error between simulated and actual event-based systems. We present the conventional techniques used in the fixed step-size simulations of the basic integrator block with reset performed in between the iteration steps. Among the issues discussed is the adverse phenomenon known as reset walk. We also propose a new set of tools in the form of the RT-events blockset. The important blocks of the RT-events blockset are succinctly explained, and three numerical examples illustrating the effectiveness of the new simulation tools are given, including a closed-loop V-6 engine system
Keywords: RT-events blockset; Simulink toolbox; V6 engine system; Digital simulation; Event-based systems; Fixed step-size simulations; Integrator block; Iteration steps; Reset walk